Comparison of haemodynamic parameters in two different geriatric age groups undergoing cemented bipolar hemiarthroplasty - Patil, Shruti Shrikant; Kotwani, Manish; Lele, Smita S.; Dhamangaonkar, Anoop C. (International Journal of Research in Medical Sciences, 2019)
Background: To conduct a prospective observational study to compare the haemodynamic changes in two age groups, group A: 60-75yrs and group B: >75yrs during cemented bipolar hemiarthroplasty for hip fractures under spinal anaesthesia. Methods: Patients of either sex belonging to above two groups, with no contra-indications for central neuraxial block received spinal anesthesia at lumbar level. Heart Rate (HR), Systolic Blood Pressure(SBP), Diastolic Blood Pressure(DBP) and Mean Arterial Pressure(MAP), pulse pressure variability(PPV), arterial oxygen saturation (SpO2), Electrocardiogram for any changes and nasal end tidal CO2 (EtCO2) were recorded at the following time points: baseline(on table), after giving spinal, after giving surgical position, at the start of surgery, at femoral canal reaming, immediately after cement insertion, every 2 minutes after cement insertion, femoral joint reduction and the end of the surgery. Hypotension, bradycardia, arrythmias, desaturation or unexpected loss of consciousness occurring in peri-cementation period suggestive of ‘Bone cement implantation syndrome’(BCIS) or any other adverse event was recognized and treated. Results: The SBP, HR, PPV, ETCO2, SPO2 and incidence of adverse events; were comparable in both the groups. The difference in the DBP and MAP was statistically significant. Conclusions: The difference in the occurrence of haemodynamic alterations was more in the older age group. Continuous vigilant monitoring during bipolar hemiarthroplasty is required.